Psychometric properties of the Chinese version of the recovery locus of control (RLOC) Scale among patients with myocardial infarction. Issue 6 (23rd July 2020) - Li, Yuli; Kong, Dong; Wang, Wei; Zhu, Yanhua; Liu, Xiaoqin
Abstract: Aim: To translate the RLOC Scale into Chinese and test its psychometric properties in the Chinese patients with myocardial infarction (MI). Design: A cross‐sectional design was used. Methods: A convenience sample of 233 patients with MI who have undergone percutaneous coronary intervention and were ready for discharge were recruited in a level A tertiary hospital of Shandong Province from January 2019 to April 2019. Data were analysed using item analysis, internal consistency reliability and exploratory factor analysis. Results: Two factors—external RLOC and internal RLOC—were extracted, accounting for 70.5% of the variance. Cronbach's alpha for the Chinese version of RLOC Scale was 0.80 and for the two factors was 0.92 and 0.76, respectively. The Chinese version of RLOC Scale showed satisfactory reliability and validity, which can be used to measure the ability of recovery locus of control in Chinese patients with MI.